Geomorphological component of volcanic geoheritage of Kouoptamo, Cameroon Volcanic Line: Geoconservation and perspectives for geotourism industry - Luc Achille Ziem A Bidias; Sahada Mouchili Nguegni; Dieudonné Charles Isidore Ilouga; Hermine Suzinie Kenna; Amidou Moundi; Pierre Kamgang (International Journal of Geoheritage and Parks, 2023)
This study was conducted in Kouoptamo, located in the Noun Plain in Western Cameroon, with the main objective of inventorying and evaluating the geological heritage, and promoting the protection and geoconservation of geosites, and their use in geotourism development. Geosites in the region include dammed lakes (Petpenoun lakes), maars (Sanka Ndoumkain Maar, Tchoua Maar), scoria cones (Nkoambeng, Kechuentim, Ngouen volcanoes), a dome (Njigoumbé Dome) and a managed natural area (Petponoun Domain). Most geosites have a high scientific, aesthetic and educational value. The method used for the inventory and assessment of geosites in this work is according to Reynard, et al. (2016), which is more suitable for geological heritage on a regional scale. The scientific value in this method is composed of four criteria, namely rarity, representativeness, integrity and palaeogeographical interest. Each of these criteria is evaluated independently by a numerical score ranging from 0 (nil) to 1 (very high) in intervals of 0.25. The overall average scientific value of the Kouoptamo geosites is 0.77. Nkoambeng Volcano has the highest scientific value (0.88), followed by Tchoua Maar, Sanka Ndoumkain Maar, Njigoumbé Dome and Ngouen Volcano, all of which score 0.81, while Kechuentim Volcano and Petpenoun Domain score 0.75 and 0.69, respectively. The integrity of several of these geosites is preserved, mainly the Petpenoun lakes, the Tchoua Maar, and the Sanka Ndoumkain Maar. Geosites such as Sanka Ndoumkain Maar, Tchoua Maar, Njigoumbé Dome and the Nkoambeng, Kechuentim, and Ngouen volcanoes are representative of the regional geomorphology. Artisanal quarries (Nkoambeng Volcano) and industrial quarries (Njigoumbé Dome), as well as agro-pastoral activities, tend to degrade these geosites, which in general do not benefit from any legal protection. It is strongly recommended that geoconservation policies be adopted for these geosites, in order to preserve and develop these sites for their considerable geotourism potential while taking into account the current resource and land usage to find an optimum, sustainable strategy.